Tìm x biết:\(|x-3|=\left|4-x\right|\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left|x-1\right|+2\left|x-2\right|+3\left|x-3\right|+4\left|x-4\right|+5\left|x-5\right|+20x=0\left(1\right)\)
TH1: x<1
(1) trở thành 1-x+2(2-x)+3(3-x)+4(4-x)+5(5-x)+20x=0
=>\(1-x+4-2x+9-3x+16-4x+25-5x+20x=0\)
=>\(5x+55=0\)
=>x=-11(nhận)
TH2: 1<=x<2
Phương trình (1) sẽ trở thành:
\(x-1+2\left(2-x\right)+3\left(3-x\right)+4\left(4-x\right)+5\left(5-x\right)+20x=0\)
=>\(x-1+4-2x+9-3x+16-4x+25-5x+20x=0\)
=>\(7x+53=0\)
=>\(x=-\dfrac{53}{7}\left(loại\right)\)
TH3: 2<=x<3
Phương trình (1) sẽ trở thành:
\(x-1+2\left(x-2\right)+3\left(3-x\right)+4\left(4-x\right)+5\left(5-x\right)+20x=0\)
=>\(x-1+2x-4+9-3x+16-4x+25-5x+20x=0\)
=>\(11x+45=0\)
=>\(x=-\dfrac{45}{11}\left(loại\right)\)
TH4: 3<=x<4
Phương trình (1) sẽ trở thành:
\(x-1+2\left(x-2\right)+3\left(x-3\right)+4\left(4-x\right)+5\left(5-x\right)+20x=0\)
=>\(x-1+2x-4+3x-9+16-4x+25-5x+20x=0\)
=>\(-3x+27=0\)
=>x=9(loại)
TH5: 4<=x<5
Phương trình (1) sẽ trở thành:
\(\left(x-1\right)+2\left(x-2\right)+3\left(x-3\right)+4\left(x-4\right)+5\left(5-x\right)+20x=0\)
=>\(x-1+2x-4+3x-9+4x-16+25-5x+20x=0\)
=>\(25x-5=0\)
=>x=1/5(loại)
TH6: x>=5
Phương trình (1) sẽ trở thành:
\(\left(x-1\right)+2\left(x-2\right)+3\left(x-3\right)+4\left(x-4\right)+5\left(x-5\right)+20x=0\)
=>\(x-1+2x-4+3x-9+4x-16+5x-25+20x=0\)
=>35x-55=0
=>x=55/35(loại)
![](https://rs.olm.vn/images/avt/0.png?1311)
(x-1)^3-(x+3)(x^2-3x+9)+3(x^2-4)=2
=>x^3-3x^2+3x-1-x^3-27+3x^2-12=2
=>3x-40=2
=>x=42/3=14
![](https://rs.olm.vn/images/avt/0.png?1311)
a/ \(x=\dfrac{-5}{12}\)
b/ \(x\approx-1,9526\)
c/ \(x=\dfrac{21-i\sqrt{199}}{10}\)
d/ \(x=\dfrac{-20}{13}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1: Ta có: \(4x^2-36=0\)
\(\Leftrightarrow\left(x-3\right)\left(x+3\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=3\\x=-3\end{matrix}\right.\)
2: Ta có: \(\left(x-1\right)^2+x\left(4-x\right)=11\)
\(\Leftrightarrow x^2-2x+1+4x-x^2=11\)
\(\Leftrightarrow2x=10\)
hay x=5
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta thấy:\(\begin{cases}\left|x-1\right|\ge0\\\left|x-2\right|\ge0\\\left|x-3\right|\ge0\end{cases}\)
\(\Rightarrow\left|x-1\right|+\left|x-2\right|+\left|x-3\right|\ge0\)
\(\Rightarrow VT\ge0\Rightarrow VP\ge0\)
\(\Rightarrow4\left(x-4\right)\ge0\Rightarrow x-4\ge0\Rightarrow x\ge4\)
\(\Rightarrow\left(x-1\right)+\left(x-2\right)+\left(x-3\right)=4\left(x-4\right)\)
\(\Rightarrow3x-6=4x-16\)
\(\Rightarrow x=10\) (thỏa mãn)
Vậy \(x=10\)
![](https://rs.olm.vn/images/avt/0.png?1311)
(2x+3)(x-4)+(x-5)(x-2)=(3x-5)(x-4)
<=.2x2-8x+3x-12+x2 -2x-5x+10=3x2-12x-5x+20
<=>5x=22
<=>x=22/5
vay